How we teach science : what's changed, and why it matters - Rudolph, John L., 1964- (Cambridge, Massachusetts : Harvard University Press, 2019)
The science taught in high schools-Newton's theory of universal gravitation, basic structure of the atom, cell division, DNA replication-is accepted as the way nature works. What is puzzling is how this precisely specified knowledge could come from an intellectual process-the scientific method-that has been incredibly difficult to describe or characterize with any precision. Philosophers, sociologists, and scientists have weighed in on how science operates without arriving at any consensus. Despite this confusion, the scientific method has been one of the highest priorities of science teaching in the United States over the past 150 years. Everyone agrees that high school students and the public more generally should understand the process of science, if only we could determine exactly what it is. From the rise of the laboratory method in the late nineteenth century, through the "five step" method, to the present day, John Rudolph tracks the changing attitudes, methods, and impacts of science education. Of particular interest is the interplay between various stakeholders: students, school systems, government bodies, the professional science community, and broader culture itself. Rudolph demonstrates specifically how the changing depictions of the processes of science have been bent to different social purposes in various historical periods. In some eras, learning about the process of science was thought to contribute to the intellectual and moral improvement of the individual, while in others it was seen as a way to minimize public involvement (or interference) in institutional science. Rudolph ultimately shows that how we teach the methodologies of science matters a great deal, especially in our current era, where the legitimacy of science is increasingly under attack.--
From textbook to laboratory -- The laboratory in practice -- Student interest and the new movement -- The scientific method -- Problems and projects -- The war on method -- Origins of inquiry -- Scientists in the classroom -- Project 2061 and the nature of science -- Science in the standards era.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed April 22, 2019).
JSTOR
Keywords: Science -- Study and teaching (Secondary) -- United States -- History; Science -- Methodology -- Study and teaching (Secondary) -- United States -- History; Education -- Social aspects -- United States -- History; Sciences -- Étude et enseignement (Secondaire) -- États-Unis -- Histoire; Sciences -- Méthodologie -- Étude et enseignement (Secondaire) -- États-Unis -- Histoire; SCIENCE -- Study & Teaching; Education -- Social aspects; Science -- Methodology -- Study and teaching (Secondary); Science -- Study and teaching (Secondary); United States; Electronic books; History